Transcriptomic profiling of watermelon (Citrullus lanatus) provides insights into male flowers development - Ying-chun ZHU; Gao-peng YUAN; Sheng-feng JIA; Guo-lin AN; Wei-hua LI; De-xi SUN; Jun-pu LIU (Journal of Integrative Agriculture)
Watermelon (Citrullus lanatus (Thunb.) Matsum. & Nakai) is an important cucurbit crop grown worldwide. Watermelon fruit quality, fertility, and seed-setting rate are closely related to male flower development. In this study, the different developmental stages of flower buds of the watermelon cultivar ‘Xinteda Zhengkang 9’ were distinguished by cytological observation, and transcriptome sequencing analysis was performed subsequently. Acetocarmine staining of anthers was performed and the longitudinal and transverse diameters of the unopened male flower buds were measured. Cytological observations of anthers at different developmental stages showed that the anther grew from the tetrad to the mature stage, and the longitudinal and transverse diameters of the flower buds increased. The length of the male flower buds also changed significantly during development. Transcriptome sequencing analysis at four periods, the tetrad (A group), mononuclear (B group), dikaryophase (C group), and mature stages (D group). A total of 16 288 differentially expressed genes (DEGs) were detected in the four stages, with the prolongation of developmental stages, the number of DEGs increased gradually in the comparison groups, there was 2 014, 3 259, 4 628, 1 490, 3 495 and 1 132 DEGs revealed in six comparison groups (A-vs.-B, A-vs.-C, A-vs.-D, B-vs.-C, B-vs.-D, and C-vs.-D), respectively. Gene Ontology (GO) and KEGG enrichment analysis showed that the DEGs were mainly enriched in cellular component and starch and sucrose metabolism, phenylpropanoid biosynthesis and pentose sugar, etc. Finally, we completely screened 59 DEGs in the six comparison groups, interestingly, we found one pollen-specific protein (Cla001608) that was significantly down-regulated (the value of log2Fold Change up to 17.32), which indicated that it may play an important role in the development of male flowers. This work provides insight into the molecular basis of the developmental stages of male flowers in watermelon and may aid in dominant cross breeding.